Algorithms for Operational Planning of Agricultural Field Operations - Jensen, Martin Andreas Falk (Technical Report Mechanical Engineering, 2013)
The report describes the current project activities on the development of optimization methods for planning agricultural field operations and on the estimation of the potential benefits for farmers by comparing optimized plans with conventional ones. The complete activities include: 1) The GNSS-based monitoring and recording of 5 large scale harvesting operations executed by fleets of agricultural machinery (E.g. Maize harvesting executed by 1 forage harvester and 5 transport carts and grain harvesting executed by 3 combines and 3 transport carts). 2) The development of a method for the automatic extraction of performance statistics from GNSS recordings of multiple-machinery operations. Classification algorithms have been created able to automatically classify the task time elements based on the recordings from GNSS loggers. 3) The development of a path planning method for transport units supporting harvesting operations. The approach incorporated i) the optimization criterions of time or travelled distance; ii) the generation of paths for both in-field and between fields movements of the transport units; and iii) the adoption of restricted movements as imposed by the controlled traffic farming concept.